2009
DOI: 10.1111/j.1445-2197.2009.05109.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laparoscopic surgery on the long‐term outcomes for patients with rectal cancer

Abstract: Laparoscopic surgery did not adversely affect the long-term oncological outcome for patients with rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Minimally invasive surgery for colorectal disease has gained popularity because it can result in better short‐term and non‐inferior long‐term outcomes than conventional open surgery . To advance minimally invasive surgical techniques, single‐incision laparoscopic surgery (SILS) was developed to minimize incision‐related pain and complications while maximizing cosmetic effect(s).…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery for colorectal disease has gained popularity because it can result in better short‐term and non‐inferior long‐term outcomes than conventional open surgery . To advance minimally invasive surgical techniques, single‐incision laparoscopic surgery (SILS) was developed to minimize incision‐related pain and complications while maximizing cosmetic effect(s).…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery has shown better short‐term outcomes than open procedures , with no differences in oncologic parameters and no long‐term disadvantages . Some studies have even identified laparoscopic surgery as an independent factor associated with reduced local recurrence . However, widespread use of laparoscopic mesorectal excision with a conventional approach is limited by technical drawbacks: fixed instrument tips, limited dexterity of the instruments, two‐dimensional view and poor ergonomic position, all of them contributing to a steep and long learning curve .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to preserve the anal sphincter in very low rectal cancer. With the understanding of the spreading pathway of low rectal cancer and development of the double stapling technique and intersphincteric resection, the frequency of sphincter preserving surgery has increased rapidly from 20% to 90% in the past 20 years [31].…”
Section: Anal Sphincter-saving Surgery In Low Rectal Cancermentioning
confidence: 99%